Development of a set of community-informed Ebola messages for Sierra Leone. - John Kinsman; Kars de Bruijne; Alpha M Jalloh; Muriel Harris; Hussainatu Abdullah; Titus Boye-Thompson; Osman Sankoh; Abdul K Jalloh; Heidi Jalloh-Vos (Public Library of Science (PLoS), 2017)
The West African Ebola epidemic of 2013-2016 was by far the largest outbreak of the disease on record. Sierra Leone suffered nearly half of the 28,646 reported cases. This paper presents a set of culturally contextualized Ebola messages that are based on the findings of qualitative interviews and focus group discussions conducted in 'hotspot' areas of rural Bombali District and urban Freetown in Sierra Leone, between January and March 2015. An iterative approach was taken in the message development process, whereby (i) data from formative research was subjected to thematic analysis to identify areas of community concern about Ebola and the national response; (ii) draft messages to address these concerns were produced; (iii) the messages were field tested; (iv) the messages were refined; and (v) a final set of messages on 14 topics was disseminated to relevant national and international stakeholders. Each message included details of its rationale, audience, dissemination channels, messengers, and associated operational issues that need to be taken into account. While developing the 14 messages, a set of recommendations emerged that could be adopted in future public health emergencies. These included the importance of embedding systematic, iterative qualitative research fully into the message development process; communication of the subsequent messages through a two-way dialogue with communities, using trusted messengers, and not only through a one-way, top-down communication process; provision of good, parallel operational services; and engagement with senior policy makers and managers as well as people in key operational positions to ensure national ownership of the messages, and to maximize the chance of their being utilised. The methodological approach that we used to develop our messages along with our suggested recommendations constitute a set of tools that could be incorporated into international and national public health emergency preparedness and response plans.